2016
DOI: 10.1080/14767058.2016.1242124
|View full text |Cite
|
Sign up to set email alerts
|

Different routes and forms of uterotonics for treatment of retained placenta: a randomized clinical trial*

Abstract: Although we aimed to exploit the advantage of certain drug over another, all seemed to have close efficacy but it would be important that further research should highlight availability, cost, ease of administration and storage requirements to determine which agent would best be used in this clinical scenario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…1). Seven studies met the inclusion criteria [12][13][14][15][16][17][18] ; nine trials were excluded because they were not randomized controlled trials (n=6), were not original articles (n=2), or were a preliminary report (n=1). The included studies are described in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Seven studies met the inclusion criteria [12][13][14][15][16][17][18] ; nine trials were excluded because they were not randomized controlled trials (n=6), were not original articles (n=2), or were a preliminary report (n=1). The included studies are described in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…In all studies, the outcomes had a high risk of bias according to the Cochrane Risk of Bias Domains (Table S3). For the random sequence generation domain, only four trials [12][13][14][15] appropriately reported the method used and were assessed as low risk of bias. For allocation concealment, five trials [14][15][16][17][18] adequately implemented a valid concealment of allocation method by using sequentially numbered sealed envelopes or containers with a similar appearance, making selection bias at enrollment unlikely.…”
mentioning
confidence: 99%
“…By contrast, the authors of another study reported that carbetocin had the same effectiveness as oxytocin at lower doses and needed less time to be effective. Conversely, misoprostol needed the longest period to reach sufficient uterine contractility [17]. No differences in effectiveness were reported for an intravenous administration of 100 μg of carbetocin and 5 IU of oxytocin [18].…”
Section: Preventionmentioning
confidence: 96%
“…Obviously, pharmacologic treatment should be introduced simultaneously -intravenous 10-30 IU of oxytocin or 100 µg of intravenous bolus of carbetocin, with similar clinical effectiveness (blood loss, severe postpartum hemorrhage, blood products transfusions). On the other hand few studies has shown higher effectiveness (amount of blood loss and the need for other uterotonics) of 100 µg carbetocin vs 5 IU oxytocin in EPH management [17].…”
Section: Treatmentmentioning
confidence: 99%
“…[11][12][13] Also, in cases with retained placenta it may have a role in management of associated bleeding which mostly result from atony. 14,15 In the field of gynecology, misoprostol could be used for induction of cervical ripening before office gynecological procedures. [16][17][18] This could decrease the associated pain induced by transcervical passage of instruments.…”
Section: Introductionmentioning
confidence: 99%